Critical sharp front for doubly nonlinear degenerate diffusion equations with time delay. (7th July 2022) - Xu, Tianyuan; Ji, Shanming; Mei, Ming; Yin, Jingxue
Abstract: This paper is concerned with the critical sharp travelling wave for doubly nonlinear diffusion equation with time delay, where the doubly nonlinear degenerate diffusion is defined by ( ( u m ) x p − 2 ( u m ) x ) x with m > 0 and p > 1. The doubly nonlinear diffusion equation is proved to admit a unique sharp type travelling wave for the degenerate case m ( p − 1) > 1, the so-called slow-diffusion case. This sharp travelling wave associated with the minimal wave speed c *( m, p, r ) is monotonically increasing, where the minimal wave speed satisfies c *( m, p, r ) < c *( m, p, 0) for any time delay r > 0. The sharp front is C 1 -smooth for 1 p − 1 < m < p p − 1, and piecewise smooth for m ⩾ p p − 1 . Our results indicate that time delay slows down the minimal travelling wave speed for the doubly nonlinear degenerate diffusion equations. The approach adopted for proof is the phase transform method combining the variational method. The main technical issue for the proof is to overcome the obstacle caused by the doubly nonlinear degenerate diffusion.